Penyebaran Yudaisme di Masa Intertestamental Dari Sudut Pandang Peristiwa Pentakosta Kis 2:9-11 - Setiawan, Hanny (Pusat Studi Pentakosta Indonesia, 2021)
Acts 2:9-11 shows a list of the nations who were present at Pentecost. This article examines the relationship between these nations and the spread of Judaism during intertestamental periods. The study was conducted by looking at history with a focus on the pattern of the spread of Judaism from one era to another, and the pattern of geographical distribution. Based on these patterns, the research results of this article conclude two main things: first, the presence of these nations has become part of God's plan to fulfill the Great Commission (Matthew 28:19-20), and the Pentecostal Commission (Acts 1: 8); second, the Jewish education system after the exile of 586 BC was the key to the successful spread of Judaism in the Intertestamental Period.Kisah Para Rasul 2:9-11 memperlihatkan daftar bangsa-bangsa yang hadir dalam peristiwa Pentakosta. Artikel ini meneliti hubungan antara bangsa-bangsa tersebut dengan penyebaran Yudaisme selama masa intertestamental. Penelitian dilakukan dengan melihat sejarah dengan fokus kepada pola penyebaran Yudaisme dari satu era kepada era lain, dan pola penyebaran secara geografis. Berdasarkan pola-pola tersebut, hasil penelitian artikel ini menyimpulkan dua hal utama : pertama, kehadiran bangsa-bangsa tersebut sudah menjadi bagian dari rencana Allah untuk memenuhi Amanat Agung (Mat 28:19-20), dan Amanat Pentakosta (Kisah Para Rasul 1:8); kedua, sistem pendidikan Yahudi setelah masa pembuangan 586 BC adalah kunci keberhasilan penyebaran Yudaisme di Masa Intertestamental.